2019
DOI: 10.1021/acscatal.9b01370
|View full text |Cite
|
Sign up to set email alerts
|

Low-Coordinate NHC–Zinc Hydride Complexes Catalyze Alkyne C–H Borylation and Hydroboration Using Pinacolborane

Abstract: Organozinc compounds containing sp, sp 2 and sp 3 C-Zn moieties undergo transmetalation with pinacolborane (HBPin) to produce Zn-H species and organoboronate esters (RBPin). This Zn-C/H-B metathesis step is key to enabling zinc catalyzed borylation reactions, with it used in this work to develop both terminal alkyne C-H borylation and internal alkyne hydroboration. These two conversions can be combined in one-pot to achieve the zinc catalyzed conversion of terminal alkynes to 1,1-diborylated alkenes without is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
90
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(100 citation statements)
references
References 72 publications
9
90
0
1
Order By: Relevance
“…Indeed, event though many reports followed pioneering works by Smith, Hartwig on C−H borylation, these methods are limited to C(sp 2 )−H and C(sp 3 )−H activation, and only a few reported C(sp)−H dehydrocoupling. In addition to Ozerov's seminal paper, it has been shown that dehydrocoupling can be catalyzed by Zn(OTf) 2 , NHC‐Zn (NHC: N‐heterocyclic carbene), (CAAC)CuX (CAAC: cyclic (alkyl)(amino)carbene) or Fe(OTf) 2 ; the borylating agent being pinacolborane (HBpin) or 1,8‐diaminonaphthalenylborane (HBdan).…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, event though many reports followed pioneering works by Smith, Hartwig on C−H borylation, these methods are limited to C(sp 2 )−H and C(sp 3 )−H activation, and only a few reported C(sp)−H dehydrocoupling. In addition to Ozerov's seminal paper, it has been shown that dehydrocoupling can be catalyzed by Zn(OTf) 2 , NHC‐Zn (NHC: N‐heterocyclic carbene), (CAAC)CuX (CAAC: cyclic (alkyl)(amino)carbene) or Fe(OTf) 2 ; the borylating agent being pinacolborane (HBpin) or 1,8‐diaminonaphthalenylborane (HBdan).…”
Section: Methodssupporting
confidence: 93%
“…The catalytic addition of silver alkynidet oiPrO-Bpin (pin = pinacol) was reported in 2014, [5] and the first dehydrocoupling using Ir/Pd pincerc omplexes [6] was described only in 2013. Indeed, event though many reports [7] followed pioneering works by Smith, [8] Hartwig [9] on CÀHb orylation,t hese methodsa re limited to C(sp 2 )À Ha nd C(sp 3 )ÀHa ctivation,a nd only af ew reported C(sp)ÀH dehydrocoupling.I na ddition to Ozerov's seminal paper, it has been shown that dehydrocoupling can be catalyzed by Zn(OTf) 2 , [3,10] NHC-Zn (NHC:N -heterocyclic carbene), [11] (CAAC)-CuX (CAAC:c yclic (alkyl)(amino)carbene) [12] or Fe(OTf) 2 ; [13] the borylating agent being pinacolborane (HBpin) or 1,8-diaminonaphthalenylborane (HBdan).Earth-abundant metal catalysis has recently gained major interest, including catalysis using Group 2o rganometallic complexes. [14] In all previously described cases,h owever,t he reaction between ab orane and earth-alkali complexes resulted in the formation of metalh ydrides that subsequently reacted with terminal alkynes through hydrometallation.T he following transmetalation to the boron would then lead to alkenylboranes, resulting from the formal hydroboration of the triple bond.…”
mentioning
confidence: 99%
“…The first metal‐catalyzed diboration of alkynes was reported by Suzuki and Miyaura in 1993 using a Pt catalyst, and significantly improved Pt catalyst systems were reported by our group . During the last few years, Pd, Cu, Co, Fe, Zn, and metal‐free systems were reported for the diboration of alkynes, which provide practical and economic alternatives to the Pt‐catalyzed processes (Scheme b) . However, the availability of diverse multiborylalkenes is quite limited because of the lack of efficient and versatile synthetic methods.…”
Section: Methodsmentioning
confidence: 99%
“…[15] During the preparation of this manuscript, Ingleson and co-workersr eported zinc-catalysed CÀHb orylation of terminal alkynesa nd the hydroboration of internal alkynes. [16] Although there are excellent examples related to the Zn-catalysed borylation of organic substrates reported, the Zn-catalysed hydroboration of alkynes is scarcely explored. Herein, we are reporting as imple and efficient zinc catalyst for regio-and chemoselective hydroboration of terminal alkynes.…”
mentioning
confidence: 99%